Respostas

2014-07-07T15:31:54-03:00
[4-(-   \frac{1}{2} ^{2}  ) +(   \frac{-3}{2} ^{2}  )] -1 
[4 -( \frac{1}{4} )÷ 3  +  \frac{9}{4} ] - 1
[ 4 - ( \frac{1}{4} × \frac{1}{3} ) +  \frac{9}{4} ] - 1
[ 4 - ( \frac{1}{12} ) +  \frac{9}{4} ] - 1
 \frac{48}{12}  \frac{1}{12}  \frac{27}{12} ] - 1
 \frac{74}{12} - 1
 \frac{74}{12}  \frac{12}{12} = \frac{62}{12} = \frac{31}{6}
2 3 2
A melhor resposta!
2014-07-07T16:00:17-03:00
Y = [4 - (-1/2)² ÷ 3 + ( - 3/2)²] - 1
y = [ 4 - (1/4) ÷ 3+ (9/4)] -1
y =  [4 - 1/4 ÷ 3 + 9/4] - 1
y = [ 4 - 1/4·3/1 + 9/4 ] - 1
y = [ 4 - 3/4 + 9/4 ] -1
y = [ 4 + 6/4 ] - 1
y = [ 4/1 + 6/4] -1
M.M.C   y = [ 16/4 + 6/4] -1
y = [ 22/4 ] -1
y = 5.5 -1
y = 4.5
4 2 4